Pelatihan Akor Dasar Untuk Meningkatkan Kemampuan Bermain Gitar Pada Anak Autis - Andi Rahmat Almuhajir BB; Dwiyatmi Sulasminah; Bastiana Bastiana (JURNAL ORTO DIDAKTIKA, 2023)
This study examines the process of basic chord training in class VII autistic children at SLB Negeri 1 Makassar. The purpose of this study is to find out: 1) Overview of guitar playing facilities at school and at home. 2) An overview of the basic chord training process in class VII autistic children at SLB Negeri 1 Makassar. 3) Obstacles faced in the basic chord training process in class VII autistic children at SLB Negeri 1 Makassar. This research approach is qualitative with a type of description research. Data collection techniques through interviews, observations and videos. Data analysis techniques through reduction, display, and data verification. The results showed that the basic chord training process for autistic children in class VII at SLBN 1 Makassar: 1) The facilities and infrastructure for playing guitar in schools are complete, but there is no special training for guitar playing for MK. 2) There are no guitar playing facilities and infrastructure at home. 3) Basic chord training is trained by researchers, by playing the guitar and singing the song